Antagonistic response regulators spatially regulate receptor methylation in the Pseudomonas aeruginosa Pil-Chp surface sensing system - Ramiro Patino; Marco J. Kühn; Henriette Macmillan; Yuki F. Inclan; Ivan Chavez; Alexandre Persat; Joanne N. Engel (Cell Reports)
Summary: Most bacterial chemosensory systems encode enzymes that are predicted to methylate and demethylate their chemoreceptors to control signaling activity. Here, we show that a predicted methyltransferase (PilK) and methylesterase (ChpB) methylate and demethylate, respectively, the chemoreceptor PilJ in the Pseudomonas aeruginosa (P. aeruginosa) Pil-Chp surface sensing system. PilJ methylation modulates the amplitude of cAMP production and the frequency of twitching motility reversals, outputs of Pil-Chp signaling. Dynamic imaging of fluorescent fusion proteins in individual twitching cells reveals that PilK and ChpB localize to opposite poles, with PilK at the lagging pole and ChpB at the leading pole. These enzymes switch poles upon bacterial reversals, a process dependent on the Pil-Chp response regulators PilG and PilH. Our results suggest that the PilJ population at each pole exists in dynamic and opposite methylation states that may reset the PilJ signaling activity at each pole during P. aeruginosa surface sensing, a key feature of adaptation.